New Kinetic Spectrophotometric Method for Determination of Fexofenadine Hydrochloride in Pharmaceutical Formulations. (28th June 2014) - Ashour, Safwan; Khateeb, Mouhammed
Abstract : A simple and sensitive kinetic spectrophotometric method was developed for the determination of fexofenadine hydrochloride in bulk and pharmaceutical preparations. The method is based on a kinetic investigation of the oxidation reaction of fexofenadine using alkaline potassium permanganate as an oxidizing agent at room temperature. The reaction is followed spectrophotometrically by measuring the increase of absorbance owing to the formation of manganate ion at 610 nm. The initial rate and fixed time (at 15 min) methods are utilized for construction of calibration graphs. All the reaction conditions for the proposed method have been studied. The linearity range was found to be 2.5–50.0 μ g mL −1 with detection limit of 0.055 μ g mL −1 for both initial rate and fixed time methods. The proposed method was applied successfully for the determination of fexofenadine in pharmaceutical formulations; the percentage recoveries were 99.98–101.96%. The results obtained were compared statistically with those obtained by the official method and showed no significant differences regarding accuracy and precision.